Analysis of Self Concept and Family Support on Marriage Readiness: A Literature Study - Cusinia, Azahra Hardi; Firman, Firman (Jurnal Aplikasi IPTEK Indonesia, 2024)
High rates of divorce, often attributed to lack of willingness to marry, point to an urgent need to investigate factors influencing such willingness. This article explores the relationship between self-concept, family support, and marriage readiness. It is based on a literature review that analysed multiple sources and previous research, which are synthesized and presented here. Therefore, a positive correlation between an individual's self-concept and the support they receive from their family is crucial in determining their readiness to enter the marriage phase. This is because the relationship between an individual's self-concept and the support they receive from their family provides a strong foundation for embarking on a new phase in life.